"Kabotyn z obwarzankiem", or propaganda of the good name of Marshal Joseph Pilsudski. Caricature, law, modern Times - Nowecki, Robert (The phenomena of propaganda and manipulation in the press, radio, television, and internet. Volume II, 2023)
Jozef Pilsudski, who was undoubtedly the most famous Polish figure of the 20th interwar period, had as many supporters behind him as he had enemies against him. The purpose of this paper is to bring to light the issue of propaganda concerning Marshal Jozef Pilsudski, which was a permanent feature of the Polish press, often finding its way into the foreign press as well. The analysis is based on the history of the image of Jozef Pilsudski over the years, which was associated with the events of the time. The paper also focuses on the key, from a legal point of view, the Law on the Protection of the Name of Józef Piłsudski - interpreting the provisions, objectives and further history of its validity and legal legacy. The result of the work in question is to present the scale of caricature and propaganda concerning the Marshal of Poland, to provide an overview of the history and consequences of legal actions directed at a specific single individual, and to examine and present possible legal analogies in Polish law.